TREATMENT COSTS EVALUATION FOR DRUG SUSCEPTIBLE AND DRUG RESISTANT TUBERCULOSIS PATIENTS IN THE UNITS OF TOMSK REGIONAL TB SERVICES - I. E. Gel'manova; N. A. Zemlyanaya; L. V. Khon; E. A. Kruk; S. P. Mishustin; G. V. Yanova (Туберкулез и болезни лёгких)
Basing on the data of capital expenses and current costs of Tomsk TB Service in 2011, prime costs of 1 month of treatment of a tuberculosis case in various units of TB Service were evaluated. The prime costs of treatment in the in-patient department as per the 1st, 2nd and 3rd regimens made 23,837 RUR per month and it was 89% higher than the cost of treatment in the day hospital (12,612 RUR), and by 173% higher than the treatment in the polyclinic (8,722 RUR), by 145% than treatment at home (9,717 RUR) and by 91% than treatment within the Sputnik program (12,499 RUR). Treatment as per the 4th regimen turned out to be the most expensive in the in-patient hospital (29,880 RUR) exceeding by 55% the treatment cost in the day center (19,336 RUR), by 112% – in the polyclinic (14,107 RUR), by 71% – treatment at home (17,512 RUR), and by 29% – Sputnik program (23,207 RUR).